Perception of Nurses Towards Documentation of Patients Records at Kabale Regional Referral Hospital. - Katushabe, Annet (Kabale University, 2024)
This research was about the perception of nurses towards documentation of patient records at Kabale Regional Referral Hospital. The study was guided by objectives which were to find out the perception of nurses towards documentation of patients' records at Kabale Regional Referral Hospital. The study was prompted by the need to find out whether there is incomplete and substandard documentation of patient records, which results in poor healthcare at Kabale Regional Referral Hospital. The study adopted a descriptive study design that utilized quantitative methods of data collection. A simple random sampling technique was used on 30 study participants. A cross-sectional research design was used and data was collected by structured, closed/open-ended questionnaires with a response rate of 100% since 30 questionnaires were distributed. Frequency distribution tables were used to present the data. Analysis of the data collected was done using Microsoft Excel. The findings of this study revealed that most participants have a positive perception towards documentation of patients' records and were aware of the significance of nurses' documenting of patients' records. The majority of nurses said that documentation of patients' records is important for the continuity of patient care and ensures a high standard of clinical care. It also allows early detection of problems, makes nurses to be respected and it is for legal interest. The study revealed that the challenges faced by nurses while documenting patient records include; busy shifts and more than one task to be done at the ward daily which affects nurses' ability to do complete and standard documentation. The study recommended that the Government and Ministry of Health should recruit many staff to the hospital. The Ministry of Health government should provide adequate documentation facilities and also employ more nurses in the hospital. Leaders in the nursing profession should emphasize the importance of documentation of patients' records and proper searching should be made for proper documentation. A social interaction group should be created for the nurses of a particular hospital or geographical location to help tackle the problems faced by nurses.